Influence of plant growth promoting rhizobacteria on nutrient concentration and productivity of Basmati rice - Meena, R. K.; Singh, Y. V.; Bana, R. S.; ', Lata (Annals of Agricultural Research, 2014)
The field experiment was conducted in Kharif season of 2011 at IARI New Delhi to study the effects of plant growth promoting rhizobacteria (PGPR) inoculation on nutrient concentration and yield of Basmati rice (cv. ’Pusa Basmati 1401’). In this study, Providencia sp. PW5 bacterial inoculant (BI), Anabaena sp. CR3 cyanobacterial inoculant (CI) and Multani mitti based BGA biofertilizer comprising composite culture of Anabaena, Nostoc, Tolypothrix and Aulosira sp. applied @ 2.0 kg/ha were evaluated in a field experiment in different combinations for integrated nutrition of rice and compared with recommended dose of nitrogen fertilizer. Results showed that the concentration of N in grain (1.38%) and straw (0.68%) were the highest with the application of 2/3 N + BI + CI + compost @ 5.0 t/ha. Application of 120 kg N/ha through chemical fertilizer significantly increased the concentrations of N in grain and straw of rice over 80 kg N/ha. Protein content in grain varied between 6.84% (N0 ) and 8.20% (2/3 N + CI + BI + compost). Highest concentration of P, K, Fe, Zn and Cu in rice grain was recorded with 2/3 N + BI + CI + compost @ 5.0 t/ha. Highest grain yield (5.02 t/ha) was obtained with the application of 2/3 N + BI + CI + compost followed by recommended dose of N (4.79 t/ha).